Expression of Angiopoietin 2 in ovarian follicles of crossbred Malabari goat - M.S. Adithian; V. Babitha; R. Uma; I. S. Sajitha; E. S. Navya (Journal of Veterinary and Animal Sciences, 2023)
Angiopoietin-2 (Ang-2) is a local ovarian growth factor belonging to the angiopoietin/Tie (tyrosine kinase with Ig and EGF homology domains) signalling pathway, one of the main pathways involved in ovarian follicular angiogenesis. The main objective of this study is to assess the differential protein expression of Ang-2 in the developmental phases of ovarian follicles of crossbred Malabari goats employing an immunohistochemical technique. Ang-2 protein expression was found in all developmental phases of ovarian follicles, including primordial, primary, small, and large antral ovarian follicles. Ang-2 was found in the granulosa cells, theca interna cells, follicular fluid (granulosa cells in the FF), endothelial cells of capillaries and germinal epithelium of the goat ovaries. The Quantitative Method-Percentage Positivity of Ang-2 expression revealed that it was higher in the initial stages of ovarian follicular development and decreased with later stages of follicular development in cross-bred Malabari goats. Moreover, the protein expression of Ang2 was found to be higher in granulosa cells (GC) than in theca interna (TI) cells of antral follicles as evident from the higher staining intensity in GC cells compared to TI cells. It is therefore concluded that the Ang-2 protein expression in ovarian follicular cells decreased with an increase in follicle size and development and based on the combined scores for immunostaining (staining intensity and the number of positive staining cells), the Ang-2 was found to be expressed more in the granulosa cell layer compared to the theca interna cells of the antral follicle in crossbred Malabari goats.